Influence of phosphorus application on growth, yield and oil quality of linola. (11th May 2016) - Irshad, Sohail; ur Rehman, Hafeez; Wahid, Muhammad Ashfaq; Saleem, Muhammad Farrukh; Basra, Shahzad Maqsood Ahmed; Saeed, Muhammad Tariq
ABSTRACT: Influence of different phosphorus (P) sources on growth, yield and oil quality of linola was evaluated when randomized in complete block design using three replications. Treatments were control (No P), hydropriming, soil phosphorus (50 kg ha −1 ), seed inoculation with phosphate solubilizing bacteria (PSB, Bacillus spp.) and seed priming with single super phosphate (2%) alone and combined with reduced soil phosphorus (25 kg P ha −1 ). Among treatments, hydropriming and seed inoculation reduced seedling 50% and mean emergence time with highest emergence index, seedling fresh and dry weights and chlorophyll contents. Seed inoculation with soil P (25 kg ha −1 ) produced highest seeds per capsule, 100-seed weight, seed and biological yield, harvest index. Maximum oil percentage, low protein contents and high cost benefit ratio with net economic returns were also found for seed inoculation combined with soil phosphorus. Nonetheless, soil phosphorus application can be reduced when seed inoculation with PSB is employed.